Stigma Kesehatan Mental Dikalangan Mahasiswa - Putri Kesyha; Tamora Br Tarigan; Ledi Wayoi; Elsa Novita (Departement of Mathematics Education, 2024)
This study investigates the pervasive stigma surrounding mental health among university students, hindering their willingness to seek help. The research, conducted through a Systematic Literature Review, analyzes ten relevant articles to understand the impact of societal attitudes on students' help-seeking behavior. Negative stereotypes and discrimination create barriers, making students hesitant to discuss their mental health concerns openly. Addressing this stigma is crucial for fostering a supportive environment. The study emphasizes the need for targeted interventions and educational campaigns to promote mental health awareness, encouraging students to seek assistance without fear of judgment